The Prevalence and Associated Death of Ventricular Arrhythmia and Sudden Cardiac Death in Hospitalized Patients With COVID-19: A Systematic Review and Meta-Analysis - Tan, Ziqi; Huang, Shan; Mei, Kaibo; Liu, Menglu; Ma, Jianyong; Jiang, Yuan; Zhu, Wengen; Yu, Peng; Liu, Xiao (Frontiers in Cardiovascular Medicine, 2022)
Background: Arrhythmia is a very common complication of coronavirus disease 2019 (COVID-19); however, the prevalence of ventricular arrhythmia and associated outcomes are not well explored. Here we conducted a systematic review and meta-analysis to determine the prevalence and associated death of ventricular arrhythmia and sudden cardiac death (SCD) in COVID-19 patients. Methods: PubMed, Cochrane Library, Embase, MdeRxiv databases were searched. Studies that could calculate the prevalence of ventricular arrhythmia/SCD during hospital admission or associated death in patients with COVID-19 were included. The study was registered with the PROSPERO (CRD42021271328). Results: A total of 21 studies with 13,790 patients were included. The pooled prevalence of ventricular arrhythmia was 5% (95%CI [confidence interval]: 4%-6%), with a relatively high SCD prevalence (1.8% in hospitalized COVID-19 and 10% in deceased COVID-19 cases). Subgroup analysis showed that ventricular arrhythmia was more common in patients with elevated cardiac troponin T (ES [effect size]: 10%, 95%CI: -0.2%-22%) and in European (ES: 20%, 95%CI: 11%-29%) populations. Besides, ventricular arrhythmia was independently associated with an increased risk of death in patients with COVID-19 (OR [odds ratio] =2.83; 95% CI: 1.78-4.51). Conclusion: Ventricular arrhythmia and SCD resulted as a common occurrence with a high prevalence in COVID-19 patients admitted to hospital. Furthermore, ventricular arrhythmia significantly contributed to an increased risk of death in hospitalized patients with COVID-19. Clinicians might be vigilant of ventricular arrhythmias for patients with COVID-19, especially for severe cases.